Adsorption of polycyclic aromatic hydrocarbons over CuZnFeAl–LDH modified by sodium dodecyl sulfate. Issue 39 (9th September 2022) - Liu, Boqing; Cao, Jingjing; Jiang, Yong; Yan, Shichang; He, Haiming; Shi, Yu; Xu, Songsong; Liang, Jinhua; Ren, Xiaoqian
Abstract : CuZnFeAl–S improves the adsorption of polycyclic aromatic hydrocarbons, which has a profound impact on environmental treatment. Abstract : Polycyclic aromatic hydrocarbons (PAHs) have received extensive attention due to being highly toxic, mutagenic, and carcinogenic organic pollutants. As a result, a series of adsorbents have been designed and developed to solve the problem. In this paper, CuZnFeAl–S has been explored as a highly efficient adsorbent for PAHs. First, CuZnFeAl–LDH was prepared using a coprecipitation method and then calcined at 500 °C to obtain CuZnFeAlO. Finally, CuZnFeAl–S was prepared by modifying CuZnFeAlO with sodium dodecyl sulfate (SDS). The physical and chemical properties of the adsorbents were characterized by XRD, N2 adsorption–desorption, SEM, ICP, FT-IR, TG-DSC, and IGC; subsequently their adsorption performance was investigated. The results show that the surface properties of CuZnFeAl–S changed from hydrophilic to hydrophobic after SDS modification, which enhanced the adsorption of PAHs obviously. The removal of naphthalene and phenanthrene on CuZnFeAl–S reached 97.3% and 90.3%, respectively. And the adsorption process of naphthalene and phenanthrene conforms to Langmuir adsorption and Freundlich adsorption, respectively. Besides, the adsorption thermodynamics indicate that the adsorption of PAHs was a spontaneous exothermic reaction. The highly efficient PAH adsorption performance of CuZnFeAl–S is the synergistic result of various molecule interactions, such as hydrogen bonding, π–π interactions, and electrostatic attraction.